FINANCIAL RATIO ANALYSIS APPLICATIONS MEDIA AS A MEASURE OF BUSINESS DEVELOPMENT - Selvia Jeane Sangian; Elly Agustina J, Skom., MMSI (Jurnal Sistem Informasi, 2003)
Financial Ratio Analysis is a form of financial statements, balance sheets and incomefee that serve as a measure of a company. Does the company is healthy or not.